STRATEGIC COMMUNICATION IN THE DIGITAL AGE: NAVIGATING THE INTERSECTION OF TECHNOLOGICAL ADVANCEMENTS, ORGANIZATIONAL DEVELOPMENT, AND PUBLIC PERCEPTION IN EDUCATIONAL INSTITUTIONS - Claudya, Samantha Elisabeth (MediaKom : Jurnal Ilmiah Komunikasi, 2025)
This research investigates organizational communication strategies in the digital age, focusing on the impact of Augmented Reality (AR) and Virtual Reality (VR) integration at Soegijapranata Catholic University's library. Qualitative methods are employed to understand organizational responses, internal dynamics, and stakeholder perceptions regarding technological advancements. The concept of Era 5.0 serves as the foundational premise, emphasizing deep technological integration into daily life. Schwab (2016) and Phillips (2019) provide contextual frameworks, while Cutlip, Center, and Broom's (2019) principles offer guidance for effective communication management amidst technological change.The study underscores the growing significance of organizational communication in higher education, particularly within library settings, aligned with Shiu's (2018) theoretical framework. Interviews with library personnel offer insights into technology application, emphasizing the strategic importance of libraries as highlighted by Fidel (2018). Stakeholder reactions, including faculty, students, and community members, are explored, drawing on insights from Wilcox (2019) and Grunig (2019) to craft outcome-oriented communication strategies.By integrating organizational communication theory, qualitative approaches, and library science, this research aims to provide actionable insights for adapting communication strategies to the digital age, especially beneficial for higher education institutions like libraries in effectively managing technological change.